Caligus (Caligidae: Siphonostomatoida) species off southern Africa with the description of C. pillaii sp. nov. - Dippenaar, Susan M.; Sebone, Makwena M. (Zootaxa, 2025)
Caligus species are mostly parasites of marine fish hosts with a few reports from fresh and brackish waters and additional reports from plankton samples with no host records. Currently there are about 279 Caligus species. Of these, 42 species have been reported from marine hosts off the southern African coast. Caligus species have been collected from a variety of hosts off South Africa and preserved in 70% ethanol. These specimens were examined and identified using stereo- and light microscopes. Nine additional Caligus species (C. asperimanus, C. antennatus, C. brevicaudus, C. elasmobranchi, C. izmiriensis, C. mulli, C. quadratus, C. cf. schlegeli and C. spinosus) are reported with distinguishing features illustrated while a new species C. pillaii n. sp. is described and illustrated. Additionally, two possible new species are also reported and illustrated as Caligus sp. 1 and Caligus sp. 2. Therefore, the number of Caligus species reported from southern African waters is raised to 52 with the addition of new host records from South African waters. Lastly, an updated key for the species groups of Caligus species is provided.